Epidemiology of Meckel's diverticulum: A nationwide population-based study in Taiwan: Characteristics of the cases from surgery between 1996 and 2013. Issue 50 (17th December 2021) - Chang, Yu-Chuan; Lai, Jung-Nien; Chiu, Lu-Ting; Wu, Meng-Che; Wei, James Cheng-Chung
Abstract : Abstract: The diverse presentation of Meckel's diverticulum (MD) is a diagnostic challenge for clinicians and most previous studies consist of single institutional case series. The aim of this study was to review the related diagnoses of MD and to investigate the epidemiological characteristics using Taiwan's National Health Insurance Research Database. We conducted an observational study using a population-based database. Patients diagnosed with MD who concurrently received intestinal surgery were identified. We analyzed the patients' demographic characteristics and relevant diagnoses using χ 2 test and 2-sample t test. We identified 2453 newly diagnosed MD patients from 1996 to 2013 and 1227 patients (50%) with intestinal obstruction, gastrointestinal bleeding, and acute appendicitis (acute abdominal pain) were defined as symptomatic. The male to female ratio was 2.4:1 with half of the patients experiencing symptomatic MD before the age of 20 years' old. The age-specific and annual incidence were calculated for all MD and symptomatic MD. Among the symptomatic MD patients, intestinal obstruction was present in 583 (48%), acute appendicitis was present in 464 (38%), and gastrointestinal bleeding was present in 283 (23%) patients. Intestinal obstruction was the most common preoperative diagnosis in the 0 to 10 years and >20 years' age groups, and acute appendicitis (acute abdominal pain) was the most common diagnosis in the 11 to 20 years' age group. This population-based 18 years' epidemiologic study described the distributions of MD symptoms among different age groups, which may help clinicians gain a better understanding of this diagnostically challenging gastrointestinal anomaly.